Propuesta de un manual de procedimientos para el Departamento de Talento Humano de la EMMAP-EP - Moreira Zambrano, María Andrea (2021)
The purpose of the investigation was to prepare a manual of processes and procedures for the Department of Human Talent of the Public Municipal Joint Venture of Potable Water of the cantons Bolívar, Junín, San Vicente, Sucre and Tosagua, to improve its management and the optimization of resources, through the methodology used with the techniques of interview and observation; and the inductive, deductive and analytical-synthetic methods, it was possible to identify each of the processes and procedures that are developed within the unit, to be reflected in a physical document in order to become a support tool for good performance of the servers, giving clear activities to follow for organizational success. With the design of the process files, flow diagrams and the descriptions of the activities of each of the processes, it was possible to clearly show the guidelines and instructions of the activities based on the specifications established by the company, in an orderly and efficient manner. easy management for the executors, therefore optimizing the development of the department's processes, which allows the institution through its servers to provide a quality and efficient service to its citizens, favoring the progress of the canton.